IPod & iTunes for dummies - Bove, Tony, 1955- (--For dummies., 2010)
An introduction to the key features of iPod, iTunes, and the iTunes music store explains how to customize one's device by setting preferences, organize a digital jukebox, copy files, burn an audio CD, preview music tracks, and search for and download songs.